The Exploratory laparotomy in Hodgkin's disease - Priario, Julio C; Martínez-Apezteguía, José L (Cirugía del Uruguay, 1972)
The paper discusses the surgeon's approach to cases of Hodgkins' disease. Surgical exploration offers advantages over other types of exploration. Surgical stages in this type of abdominal exploration are described with emphasis, on ganglia and liver biopsies. The techniqU'e · employed for performing the splenectomy is described.